2022
DOI: 10.3389/fmicb.2022.982650
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of the FAST™ System and the FAST-PBC Prep™ cartridges for speeded-up positive blood culture testing

Abstract: Performance evaluation of the FAST TM System and the FAST-PBC Prep TM cartridges for speeded-up positive blood culture testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In our study, FAST-DD led to slightly better results (CA of 98.7% for Gram positive and 97.5% for Gram negative) when compared to directly inoculated DD from PBC, which are part of our routine workflow, than the automated method using FAST-MicroScan (CA of 96.1% for both Gram positive and Gram negative). Comparable CA values were previously reported for both Gram-positive [97.4% ( 18 ), 97.7%–100% ( 19 ), and 99.5% ( 20 )] and Gram-negative bacteria [98.5% ( 18 ), 97.8%–99% ( 19 ), and 97.8% ( 20 )] where automated AST systems other than MicroScan WalkAway (i.e., bioMérieux Vitek 2 or BD Phoenix) were utilized. Given these previous studies, our study though is the first to use MicroScan WalkAway demonstrating the compatibility of this automated AST technology with the FAST System.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In our study, FAST-DD led to slightly better results (CA of 98.7% for Gram positive and 97.5% for Gram negative) when compared to directly inoculated DD from PBC, which are part of our routine workflow, than the automated method using FAST-MicroScan (CA of 96.1% for both Gram positive and Gram negative). Comparable CA values were previously reported for both Gram-positive [97.4% ( 18 ), 97.7%–100% ( 19 ), and 99.5% ( 20 )] and Gram-negative bacteria [98.5% ( 18 ), 97.8%–99% ( 19 ), and 97.8% ( 20 )] where automated AST systems other than MicroScan WalkAway (i.e., bioMérieux Vitek 2 or BD Phoenix) were utilized. Given these previous studies, our study though is the first to use MicroScan WalkAway demonstrating the compatibility of this automated AST technology with the FAST System.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding the performance of the FAST System in terms of ID, Grinberg and colleagues reported an ID concordance of 94% ( n = 201) using MALDI Biotyper as compared to colonies obtained by subculture ( 18 ). Similarly, Verroken and colleagues reported 89.5% ( n = 266) concordant ID results using the FAST System LC and MALDI Biotyper including 80 blood cultures bottles spiked with multidrug-resistant bacteria ( 19 ). Likewise, Kuo and colleagues demonstrated an accurate ID of 94.1% (272/289) using LC generated by the FAST System and MALDI-TOF MS Microflex ( 20 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The recently developed FAST system, used here on an experimental basis, allows identification and AST to be performed directly from broth cultures by removing cellular materials, proteins and other interfering substances that may be found in broth. Intended for automated processing of blood culture specimens, the FAST system has yielded promising results in early studies to support clinical use when paired with various downstream identification and AST platforms [13][14][15][16][17]. Prospective studies have found that for positive blood cultures, FAST system processing can be used to rapidly obtain correct organism identifications by MALDI-TOF in 87-96 % of cases, and AST results with ~98 % categorical agreement with standard of care AST [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Intended for automated processing of blood culture specimens, the FAST system has yielded promising results in early studies to support clinical use when paired with various downstream identification and AST platforms [13][14][15][16][17]. Prospective studies have found that for positive blood cultures, FAST system processing can be used to rapidly obtain correct organism identifications by MALDI-TOF in 87-96 % of cases, and AST results with ~98 % categorical agreement with standard of care AST [13][14][15][16][17][18]. Not only has the FAST system been shown to be highly accurate, it has also been shown by other studies to significantly reduce workflow time [17,18].…”
Section: Discussionmentioning
confidence: 99%